Does 'Dual Trigger' Increase Oocyte Maturation Rate?. (17th August 2020) - Ben-Haroush, Avi; Sapir, Onit; Salman, Lina; Altman, Eran; Garor, Roni; Margalit, Tamar; Shufaro, Yoel; Oron, Galia
Abstract: The aim of this study was to evaluate the oocyte maturation rate when GnRH-a and hCG (dual trigger) are co-administered, compared to the standard hCG trigger within the same patient. Included in the study were GnRH antagonist ICSI cycles performed in 137 patients who had a standard hCG trigger cycle and a dual trigger cycle between 1/1/2013 and 31/12/2017. The mean patient age (35.9 ± 5.6 and 35.2 ± 5.9; <0.001), FSH dose (4140 ± 2065 and 3585 ± 1858; <0.01), number of retrieved oocytes (10.3 ± 6.2 and 8.9 ± 6.1; 0.011) were higher in the dual trigger group compared to the hCG trigger group, oocyte maturation rate was identical. Maturation rate following dual trigger was significantly higher among 34 patients who had a maturation rate of <70% following hCG triggering and among 16 patients with a maturation rate <50% rate following hCG trigger (54% vs. 74%, p < .001 and 44% vs. 73%, p = .006; respectively). In conclusion, co-administration of GnRH agonist and hCG for final oocyte maturation substantially increased the oocyte maturation rate in patients with low oocyte maturation rate in their hCG triggered cycle, but not in an unselected population of patients. IMPACT STATEMENT: What is already known on this subject? The co-administration of GnRH agonist and hCG for final oocyte maturation prior to oocyte retrieval may improve IVF outcome in patients with a high proportion of immature oocytes. The few studies on dual trigger in patients with a high proportion of immature oocytes or in normal responders have shown conflicting results. What do the results of this study add? We found that co-administration of GnRH agonist and hCG for final oocyte maturation substantially increased the oocyte maturation rate in patients with low oocyte maturation rate in their hCG triggered cycle, but not in an unselected population of patients. What are the implications of these findings for clinical practice and/or further research? The results of this study implicate that in selected population with low oocyte maturation rate, there is an advantage in using dual trigger. However, larger prospective trials are warranted to better assess oocyte response in dual trigger.